1995
DOI: 10.1074/jbc.270.45.27093
|View full text |Cite
|
Sign up to set email alerts
|

RhoA and a Cytosolic 50-kDa Factor Reconstitute GTPγS-dependent Phospholipase D Activity in Human Neutrophil Subcellular Fractions

Abstract: Receptor activation of phospholipase D has been implicated in signal transduction in a variety of cells. Reconstitution of cell-free guanosine 5 -O-(3-thiotriphosphate)(GTP␥S)-dependent phospholipase D activity from human neutrophils requires protein factors in both the plasma membrane and the cytosol. We previously proposed that one of the factors is a Ras-family small molecular weight GTPase of the Rho subtype (Bowman, E. P., Uhlinger, D. J., and Lambeth, J. D. (1993) J. Biol. Chem. 268, 21509 -21512). Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…The 36-kDa protein may differ from the 50-kDa protein in h ~matopoietic cell lines [13][14][15] 7 he 36-kDa protein containing fraction (1 mg protein) prepared as i~ the legend to Table 2 was applied to a Superose 12 column x~hich had been equilibrated with buffer A [18], and eluted with the s,tme buffer at a flow rate 0.5 ml/min using an FPLC system (Pharmacia). PtdEtOH produced (dpm x 10 -3) Supernatant and particulate fractions were prepared from various rat tissues [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 36-kDa protein may differ from the 50-kDa protein in h ~matopoietic cell lines [13][14][15] 7 he 36-kDa protein containing fraction (1 mg protein) prepared as i~ the legend to Table 2 was applied to a Superose 12 column x~hich had been equilibrated with buffer A [18], and eluted with the s,tme buffer at a flow rate 0.5 ml/min using an FPLC system (Pharmacia). PtdEtOH produced (dpm x 10 -3) Supernatant and particulate fractions were prepared from various rat tissues [18].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an additional protein factor has been reported 1 aat is needed for guanosine 5'-O-(3-thiotriphosphate) 43TP-~t-S)-dependent PLD activity. PLD obtained from lematopoietic cell lines is shown to be activated by a 50-~Da soluble protein and either ARF [13,14] or RhoA [15]. ];rain PLD is also activated by a cytosolic factor in a synerr istic manner with ARF [16], and this factor has recently been ~Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…A 50-kDa factor has been shown to act synergistically with both ARF (11,12) and Rho in stimulating PLD (13). Similarly, both G proteins also act synergistically with protein kinase C␣ to activate PLD.…”
mentioning
confidence: 99%
“…Phosphatidylinositol 4,5-bisphosphate (PIP 2 ) was the first activator and a key element in establishing assays for the enzymes (6,(11)(12)(13). This was followed by the elucidation of activation by members of both the Arf (6,14) and Rho (15)(16)(17)(18)(19) families of small monomeric GTPases and by classical isoforms of protein kinase C (PKC) via a phosphorylation independent pathway (20,21). Subsequent studies with recombinant proteins in vitro have shown that PLD1 responds to all of these activators (22), while PLD2 is only stimulated by PIP 2 and Arf (9,23,24).…”
mentioning
confidence: 99%